THE EFFECT OF GIVING BETEL LEAF EXTRACT (Piper betle L.) THROUGH DRINKING WATER ON COMMERCIAL CUTTINGS OF BROILER CARCASS - I W. S., Yasa; Nuriyasa, I M.; Astawa, I P. A. (Jurnal Peternakan Tropika; Vol 9 No 1 (2021): Vol. 9 No. 1 Tahun 2021; January - april, 2021)
This study aims to determine the effect of betel leaf extract on commercial cuttings of broiler carcass. This research was conducted in Mr. Nuriyasa's, cage in Dusun Pande, Dajan Peken Village, Tabanan Regency which was conducted for four weeks. The design used was a completely randomized design (CRD) with three treatments and ten replications, each treatment unit using two broilers. The treatments given were drinking water without using betel leaf extract ( Piper betle L. ) as a control (R0), giving 2% betel leaf extract through drinking water (R1) and giving 4% betel leaf extract through drinking water (R2). The variables observed in this study were cut weight, carcass weight, percentage of carcass, percentage of commercial cuttings of carcass (breast, upper thighs, lower thighs, wings and back).The results showed that cut weight, percentage of carcass, and percentage of commercial cuttings of carcass had insignificant differences (P>0.05) between treatments. Carcass weight in the highest R2 treatment was 1,193.00 g and was significantly higher 6.47% to the control treatment (P<0.05) and 2.69% higher than treatment R1, but statistically not significantly different (P> 0.05). Based on the results of this study it can be concluded that giving up to a level of 4% betel leaf extract ( Piper betle L.) through drinking water in broilers gives the same results to cut weight, carcass percentage, chest, upper thighs, lower thighs, wings, and back. There was an increase in broiler carcass weight in the administration of 4% betel leaf extract ( Piper betle L. ).   Keywords:  drinking water, broiler, betel leaf extract, carcass , commercial cut tings of carcas .